Cognitive framing modulates emotional processing through dorsolateral prefrontal cortex and ventrolateral prefrontal cortex networks: A functional magnetic resonance imaging study. Issue 9 (4th August 2020) - Kirk, Ulrich; Lilleholt, Lau; Freedberg, David
Abstract: Introduction: In this study, we show new evidence for the role of ventrolateral prefrontal cortex‐dorsolateral prefrontal cortex (VLPFC‐DLPFC) networks in the cognitive framing of emotional processing. Method: We displayed neutral and aversive images described as having been sourced from artistic material to one cohort of subjects (i.e., the art‐frame group; n = 19), while identical images, this time identified as having been sourced from documentary material (i.e., the doc‐frame group; n = 20) were shown to a separate cohort. Results: Using functional magnetic resonance imaging (fMRI), we employed a linear parametric model showing that relative to the doc‐frame group the art‐frame group exhibited a modulation of amygdala activity in response to aversive images. The attenuated amygdala activity in the art‐frame group supported our hypothesis that reduced amygdala activity was driven by top‐down DLPFC inhibition of limbic responses. A psychophysiological interaction (PPI) analysis demonstrated that VLPFC activity correlated with amygdala activity in the art‐frame group, but not in the doc‐frame group for the contrast [Aversive > Neutral]. Conclusion: The role of the VLPFC in cognitive control suggests the hypothesis that it alongside DLPFC insulates against embodied emotional responses by inhibiting automatic affective responses. Abstract : We show that cognitive framing have neural effects on emotional processing.